How to train your dragon book 5 : how to twist a dragon$1 (Bs tale /s - Cowell, Cressida (New York : Little, Brown and Company, 2010)
When a volcano threatens to erupt and destroy everything, Hiccup must uncover Viking secrets and lead a dangerous quest that will test his courage and friendships.
Originally published in the U.K. by Hodder Children$1 (Bs Books, 2007.s
Keywords: Vikings -- Fiction; Dragons -- Fiction; Quests (Expeditions) -- Fiction; Friendship -- Fiction; Heroes -- Fiction; Humorous stories